Stages of God's creation of man in the Koran stu (Journal of the College of Education for Women, 2019)
Thanks allah and peace be upon our prophet muhammed and upon his family and hisfollowers……The name is only called by the Almighty, One of the Names of the Creator Deityfeatures and slavery. He is the idol who worshiped.The creator is derived from the creation of a sophisticated and significant from create Aharazfor crust, and tailor the gown and the end of launch on God's creation of the creature, and thisrelease was a matter of metaphor One of the names of Allah, God is the creator himself is nota partner Creator of all things, is the one who createdman from Nothingness began creating Adam peace be upon him and that he has passed thestages in the process of creation, namely: He created him from dust, and when you add waterto him became mud and then turning mud to flesh elderly any clay black, and when dried mudbecame Salsala not be untouched by the fire, and then inflatable God of his soul CreatingAdam, the first human beings. God Almighty has created man from clay Mitt not motionlessin it and make his descendants out of the bottom of the crucifixion ofwater is weak, called adrop, then turned the sperm into a piece of blood frozen called leech then turned clot to thepiece of meat small called embryo and then turned into a bone and then God meat again andthen completed his creation and filmed and enter the spirit.